Integrating modern business values and cloning: The legality, morality, and social responsibility of somatic cell nuclear transfer - Blanche A. Williams; Frank J. Cavico; Bahaudin G. Mujtaba (Advances in Management & Applied Economics, 2011)
Science and technology have catapulted the possibilities of cloning into reality. Over the past few decades, cloning has given rise to aggressive research and business opportunities that have transformed society's views on the scientific andcommercial uses, as well as abuses, of cloning. The advent of cloning, therefore, has engendered a multitude of implications and consequences that our society, legal system, religious, and scientific communities continue to struggle with. How does the public embrace, laws protect, religion condone, and morality support the research, science, and implementation of cloning? The worldwide involvement in cloning, moreover, is an indication that this practice has secured widespread recognition and influence. This paper will explore the science of cloning, the companies involved, the laws that affect it, the ethics that guide it, and the social responsibility of its participants and presence in our global society's future.
Keywords: 330; cloning; somatic cell nuclear transfer; ethics; morality and social responsibility